Effect of Caloric Restriction on Hepatic Sinusoidal System and Stellate Cells in Mice - Jian Chen; Kara King; Jian X. Zhang (Journal of Aging Research)
Aging associated changes in liver include reduced hepatic blood flow, increased number of stellate cells, and collagen deposits in perisinusoidal space. We tested the possibility of mitigating these changes with caloric restriction. Two-month-old mice were subjected to 30 percent caloric restriction for 12 months and then examined for the effect of caloric restriction on the sinusoidal network, collagen deposition, and the number of stellate cells. Using intravital fluorescence microscopy, assessments were made on sinusoidal diameter, density, volumetric flow, perfusion index, and autofluorescence of vitamin A that was primarily stored with lipid droplets in stellate cells. A significant effect was observed in the vitamin A autofluorescence of stellate cells; stellate cell associated fluorescence was diminished in terms of number and size of fluorescent spots. Caloric restriction reduced collagen deposits in liver sections and lowered the gene expression of α1-(I) collagen but not α-smooth muscle actin. No differences were detected in sinusoidal dimension measurements. Our results showed that caloric restriction was effective in ameliorating the increase in stellate cells and the mild fibrosis in old mice. However, caloric restriction had no impact on stellate cell activity level as indicated by the unaffected α-smooth muscle actin expression.